Pengaruh Penerapan Model Pembelajaran Example non Example terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Arinta Rara Kirana; Rahmawati, Fitriana (Lentera: Jurnal Ilmiah Kependidikan, 2025)
The problems studied in this study are related to the less than optimal achievement of students' mathematical problem-solving abilities. The purpose of this study was to determine the effect of the Example non Example learning model on the mathematical problem-solving abilities of class VIII students in the Even Semester of SMP Negeri 19 Bandar Lampung in the 2024/2025 Academic Year. This study used an experimental method with the population in this study being all class VIII students of SMP Negeri 19 Bandar Lampung consisting of 7 classes. While the sample was taken from two classes, namely class VIII B as the experimental class that applies the Example non Example learning model, and class VIII C as the control class that applies the conventional learning model. The sample was taken using the Cluster Random Sampling technique. To determine students' mathematical problem-solving abilities, the author conducted a test in the form of five essay questions that had previously been tested for validity and reliability. Hypothesis testing in this study used the t-hit formula and obtained t = 3,29. From the t-distribution table at a significance level of 5%, it is known that t = 1,67, so , which means that the average mathematical problem-solving ability of students using the Example non Example learning model is higher than the average mathematical problem-solving ability of students using the conventional learning model.